Recall and mathematical problem solving for students with disabilities - Kamid Kamid; Jefri Marzal; Wardi Syafmen; Rohati Rohati; Rina Kusuma Dewi (Jurnal Cakrawala Pendidikan, 2021)
This article reports on the ability of feeble-minded or mentally retarded students in mathematical recall and problem-solving processes. In particular, this study investigated whether recall ability can affect feeble-minded students' ability to work on mathematical problems. This research was conducted using a mixed-method approach with a sequential explanatory research design. The sample of this study consisted of 34 feeble-minded students. The findings show that the ability of feeble-minded students to solve mathematical problems and their recall abilities were categorized as fair Another finding is that the ability to recall had a 62.1% effect on the ability to work on mathematical problems. The contribution of this study is that feeble-minded students' ability to work on mathematical problems is greatly influenced by their ability in the mathematical recall process.